Tooth Discoloration after Using a Premixed Mineral Trioxide Aggregate-Based Endodontic Sealer (Endoseal MTA) - Kosar Dadgar; Sara Rastakhis; Jamshid Yazdani Charati; Abolfazl Hosseinnataj; Salma Omidi (Mashhad University of Medical Sciences, 2022)
Introduction: Introduction: The present study aimed to evaluate the coronal discoloration of human teeth induced by using a new Endoseal MTA compared to an AH Plus Sealer. Methods: A total of 40 premolars extracted for orthodontic reasons were used in the present study. Then, the teeth were incised in the coronal third of the root 3 mm below the cementoenamel junction. Samples were randomly allocated to two experimental groups (group 1: AH Plus sealer, group 2: Endoseal MTA) and 6 teeth as the negative control group. The color evaluation was determined at four different times: before placing sealers (T0), 1 month (T1), 3 months (T2), and 6 months (T₃) after that with an intraoral spectrophotometer. Data were analyzed using Multivariate Test and Hotelling's Trace. A P-value <0.05 was considered statistically significant. Results: The Endoseal group showed discoloration after 1 and 3 months of the placement of sealer as AH Plus sealer. Also, discoloration of the AH Plus group was higher than that of the Endoseal group after 3 months; however, it was not significant (P˃0.05). Furthermore, discoloration of the Endoseal group was significantly higher than that of the AH Plus group after 6 months (P<0.05). Discoloration tended to decrease until 6 months in both groups. Conclusion: The Endoseal group indicated discoloration which is comparable to AH Plus in 1 and 3 months; however, discoloration in the AH Plus group decreased compared to the Endoeseal MTA group after 6 months.